Antitrust issues raised by answer engines - Christophe Carugati (Bruegel, 2023)
Rapid development of generative artificial intelligence chatbots like ChatGPT is leading search engine providers to move from search to answer engines. Unlike search engines, which provide search results in the form of blue links to content creators, answer engines generate personalised answers through a conversation with end users. This revolution impacts the internet ecosystem of content creators and the digital advertising market. This paper outlines some early antitrust issues related to answer engines, from the transition from search to answer engines (sections 2 and 3) and the response competition authorities should adopt (section 4). It finds that search and answer engines complement and compete with each other. While the answer-engine market is still at an early stage of development, it already raises some competition issues in relation to data scraping, vertical integration and unfair terms and conditions. Intervention by competition authorities is more likely than not to prevent market power in this new market. In this regard, competition authorities should act to preserve dynamic competition and minimise adverse effects on content creators. Finally, the paper concludes with several research questions for future research (section 5).
Keywords: K21; L01; L04; L05; L86; 330; digital competition; antitrust; competition law; competition law andeconomics; answer engine; search engine; generative AI; ChatGPT